2022
DOI: 10.3390/su141710505
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Radon Risk Perception, Awareness, and Knowledge: Risk Communication Options

Abstract: Radon is the second leading cause of lung cancer after cigarette smoking, and research on individual risk perception of radon is crucial to prevent its health effects. In this work, we aimed to systematically review the scientific literature that has analyzed radon risk perception, awareness, and knowledge to provide insight on communication actions. For this purpose, following the PRISMA 2020 statement, we searched PubMed, Embase, and Web of Science, focusing on articles published since 2010. After the screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 79 publications
2
7
0
1
Order By: Relevance
“…Moreover, the disadvantage faced by renters, highlighted in Davis et al [32], correlates with the lower engagement in preventive practices observed in our non-homeowner participants. This highlights a disparity that could be mitigated through policy-level interventions, a perspective that aligns with the findings from both Cori et al [33] and Unni et al [28], which advocate for broader legislative support in public health initiatives. This study reinforces the existing narrative that while knowledge and perceptions are foundational to preventive health behaviours, the addition of self-efficacy is crucial [28,32,33].…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, the disadvantage faced by renters, highlighted in Davis et al [32], correlates with the lower engagement in preventive practices observed in our non-homeowner participants. This highlights a disparity that could be mitigated through policy-level interventions, a perspective that aligns with the findings from both Cori et al [33] and Unni et al [28], which advocate for broader legislative support in public health initiatives. This study reinforces the existing narrative that while knowledge and perceptions are foundational to preventive health behaviours, the addition of self-efficacy is crucial [28,32,33].…”
Section: Discussionsupporting
confidence: 56%
“…Bearth et al (2017) argue that the perceived artificiality of a risk source enhances concern, and that this tends to be the case for microplastics. Research from other domains supports this line of argumentation insofar that radon radiation has been shown to be perceived as less risky than other sources of radiation (Halpern & Warner, 1994), which could be because radon is viewed as being of natural origin (Cori et al, 2022). The perception of microplastics as being artificial and human-caused might offer an explanation of why microplastics were seen as having a strong moral component in the current sample.…”
Section: Discussionmentioning
confidence: 91%
“…Bearth et al (2017) sostienen que la artificialidad percibida de una fuente de riesgo aumenta la preocupación, y que este tiende a ser el caso de los microplásticos. La investigación en otros ámbitos respalda esta línea de argumentación, en la medida en que se ha demostrado que el riesgo por la radiación del radón se percibe como menor que el de otras fuentes de radiación (Halpern & Warner, 1994), lo que podría deberse a que el radón se considera de origen natural (Cori et al, 2022). La percepción de los microplásticos como artificiales y causados por el hombre podría ofrecer una explicación de por qué la muestra actual consideraba que los microplásticos tenían un fuerte componente moral.…”
Section: Discussionunclassified
“…Because the residential radon exposure can contribute to the onset of lung cancer in the overall population, the perception and communication of radon risks continues to receive a lot of research interest [6][7][8]. In addition, radon concentrations vary spatially depending on different geology factors and are particularly elevated in areas with phosphate rocks, metamorphic rocks and uranium ores [9].…”
Section: Introductionmentioning
confidence: 99%